The effect of periodized flywheel training on power of lower limbs - Arsenis, S.; Gioftsidou, A.; Smilios, I.; Malliou, P.; Chatzinikolaou, A. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The aim of this study was to compare the effects of semi-squat exercise with a flywheel device and free weights on parameters of physical performance. METHODS: 48 well-trained male athletes were randomly divided into three subject groups (N.=16 each), two training groups (DT and RT) and one control group (CON). The duration of the intervention program was 8 weeks with frequency 2 times per week. Squat (SJ), countermovement (CMJ) and drop jump (DJ) tests were evaluated pre- and postprogram. Additionally, sprint performance in 10 (T10) and 30 meters (T30) was evaluated. The mechanical parameters of semi-squat exercise were analyzed pre- and postintervention program. Specifically, the optimum power load (OPL) and the average power output during semi-squat were evaluated. RESULTS: Statistically significant differences showed on 1RM between RT and CON group (P<0.05). Statistically significant difference in SJ and CMJ were showed between DT and CON group. Also, DT decrease significant the time of 10m and 30m sprint in compare with CON group (P<0.05). These results demonstrate that flywheel training has similar effects with resistance training on power of lower limbs muscles. CONCLUSIONS: Flywheel training can be used as alternative training in periodized programs that aim to enhance sports performance. Finally, these findings can be useful for strength and conditioning coaches to understand the function of flywheel device and the design of resistance training programs.